Role of selected minerals in ruminal indigestion in cross-bred cattle - George Thomas (Department of Clinical Medicine, College of Veterinary and Animal Sciences, 1983)
The present investigations were taken up with the objectives to survey the incidence and seasonal dynamics of digestive disorders in cattle in Kerala, to study the associated changes in physical characters, Ph, protozoal motility and sedimatnation activity time of rumen liquor and the status of selected minerals in rumen liquor and blood in clinical cases of simple indigestion in crose – bred cattle and based on the findings in the above to modify and compare the line of therapy for the same. Date collected from selected veterinary hospitals in the field and under the Kerala Agricultural University showed that digestive disorders formed 33.10 per cent of the total of the incidence of diseases in cattle. Among the digestive disorders, cases of indigestion as a whole were 70.07 per cent and simple indigestion mostly associated with dietetic errors were 48.90 per cent. Influence of season on the incidence of these conditions was significant, being highest in summer. This could be attributed to irregularities in with non – availability of good quality fodder throughout the year and feeding cattle predominantly on dry and coarse locally available unconventional animal rations and inadequate supply of water during the season. Eight apparently healthy adult cross-bred cattle from the University Livestock Farm, Mannuthy, formed the healthy control animals (Group I). Twelve clinical cases of simple indigestion in adult cross – bred cattle divided at random into two groups of six each constituted the treatment groups (Group II and III). In Group II animals conventional therapy consisting of bitter stomachics orally and liver extract parenterally was tried. In animals of group III modified therapy comprising of bitter stomachics and ‘Anorexon’ (pfizer pvt. Ltd.) tablets orally and ‘Calborol’ (M & B pvt. Ltd.) intravenously was adopted. Course of the disease was studied and samples of rumen liquor and blood were collected for analysis on the first, fourth and seventh day of admission in the clinic. Important clinical signs of the disease were slight general depression and dullness, partial or complete loss of appetite, suspension of rumination, cessation or depressed rumen contractions, normal or pesty and scanty dung or presence of mild diarrhoes and drop in milk yield. The body temperature and rates of pulse and respiration were normal. Physical characters of the rumen liquor from cattle with simple indigestion were altered in that the colour was brownish yellow/brownish with faintly aromatic/faintly sour odour and thin/thick consistency compared to the greenish yellow colour, aromatic odour and thick consistency of rumen liquor from healthy control animals. Protozoal motility was suppressed (slow (+) to moderate (++) and SAT was prolonged to 26.16 + 1.70 minutes. Levels of calcium, phosphorus and magnesium in the rumen liquor and blood were significantly reduced (P < 0.01) in the cases studied. However, the levels of sodium and potassium did not show any significant variations before, during or after therapy. Mean calcium, phosphorus, magnesium, sodium and potassium levels of rumen liquor in affected animals were 10.20 + 0.37 mg/dl, 7.76 + 0.23 mg/dl, 5.85 + 0.20 mg/dl, 132.33 + 1.17 mEg/L and 23.93 + 1.74 mEg/L respectively and the corresponding values in blood were 10.17 + 0.096 mg/dl, 5.17 + 0.093 mg/dl, 2.12 + 0.28 mg/dl, 150.35 + 1.30 mEg/L and 4.61 + 0.13 mEg/L. Physical characters, protozoal motility and SAT of the rumen liquor have almost returned to normal ranges following therapy. Improvements in calcium, phosphorus and magnesium level in rumen liquor and blood could presumably be associated with revivel of appetite and increased intake of feed following therapy. On the basis of better clinical response as judged by early return of appetite and milk yield, better improvements in the microbial activity of rumen liquor and mineral status of rumen liquor and blood and shorter recovery period, the modified therapy was found superior to the conventional therapy for the clinical management of simple indigestion in cross – bred cattle.